2020
DOI: 10.1002/mp.14336
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo dosimetric characterization of a new high dose rate Yb brachytherapy source and independent verification using a multipoint plastic scintillator detector

Abstract: Purpose: A prototype 169 Yb source was developed in combination with a dynamic rotating platinum shield system (AIM-Brachy) to deliver intensity modulated brachytherapy (IMBT). The purpose of this study was to evaluate the dosimetric characteristics of the bare/shielded 169 Yb source using Monte Carlo (MC) simulations and perform an independent dose verification using a dosimetry platform based on a multipoint plastic scintillator detector (mPSD). Methods: The TG-43U1 dosimetric parameters were calculated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…The shield is not thick enough to attenuate the intensity of the conventional 192 Ir source, hence this radionuclide cannot be used for prostate IMBT. A radionuclide with lower energy than 192 Ir, namely 169 Yb was chosen (Famulari et al 2020b). The dynamic shield system combined with the source model presented in Famulari et al (2020a) were used in the simulations performed in this study with 169 Yb as the active source.…”
Section: Patient Data Simulation Details and Plan Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The shield is not thick enough to attenuate the intensity of the conventional 192 Ir source, hence this radionuclide cannot be used for prostate IMBT. A radionuclide with lower energy than 192 Ir, namely 169 Yb was chosen (Famulari et al 2020b). The dynamic shield system combined with the source model presented in Famulari et al (2020a) were used in the simulations performed in this study with 169 Yb as the active source.…”
Section: Patient Data Simulation Details and Plan Optimizationmentioning
confidence: 99%
“…In 2013, Webster et al (2013) published a study regarding dynamic modulated brachytherapy for rectal cancer by translating and rotating a tungsten alloy shield during the treatment. Following this study, two separate studies by Adams et al (2014) and Famulari et al (2020b) for prostate cancer and additional studies by Dadkhah et al (2015) and Morcos and Enger (2020), Morcos et al (2021) for cervical cancer investigated rotating shield brachytherapy. All these studies showed improved dose distributions when IMBT was compared to conventional brachytherapy.…”
Section: Introductionmentioning
confidence: 99%